Initial Feasibility Ground Test of a Proposed Photogrammetric System for Measuring the Shapes of Ice Accretions on Helicopter Rotor Blades during Forward Flight - Palko, R L; Cassady, P L; McKnight, R C; Freedman, R J (1984)
A ground test was accomplished to determine if a combination of standard photographic system parameters could be chosen that would allow stereophotographs to be made of the main rotor of a UH-1H helicopter in forward flight. The photographs would be used to measure the shape of ice accretions on the rotor in forward flight. During the ground test, 83 photographic pairs were obtained at three camera shutter speeds for a range of ambient light conditions from dark to complete daylight. Twenty-seven of these photographic pairs were evaluated on the AEDC analytical stereocompiler for readability. The test showed that quality photographs could be taken using standard equipment with shutter speeds of 1/30 and 1/60 sec for up to three hours per day. The test also showed that the addition of a specifically designed control circuit for synchronization at 1/500-sec shutter speed would allow testing for the complete day for most winter days. Prepared in cooperation with Calspan Field Services, Inc., Arnold AFS, TN. AEDC Div.